A review on link adaptation techniques for energy efficiency and QoS in IEEE802.11 WLAN - Aliya Syahira Mohd Anuar; Wan Norsyafizan W Muhamad; Darmawaty Mohd Ali; Suzi Seroja Sarnin; Norfishah Ab Wahab (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Link adaptation is a technique that able to adapt modulation and coding scheme (MCS) based on radio channel conditions. With the exponential increase on the wireless devices nowadays, it contributes to high energy consumption and an increase in carbon dioxide (CO2) emission which contribute to the environmental issue. Researchers have developed proposals to tackle these issues by design algorithms based on link adaptation technique. Nowadays, various link adaptation techniques have been proposed by researchers with target for either Quality of Service (QoS) enhancement as well as energy efficiency. This paper presents A Review on Link Adaptation Techniques for Energy Efficiency and QoS in IEEE802.11 WLAN. In this study, a comprehensive review of the relevant literature published that focus on link adaptation technique in IEEE 802.11 WLAN in improving the energy efficiency and maximize the QoS performance is presented. Link adaptation can be categorized into transmission power control adaptation, transmission data rate adaptation and joint rate adaptation. These adaptations are carried out according to the channel state information (CSI). CSI can be categorized into signal-to-noise ratio (SNR), bit error rate (BER), delay, and queue length.